2022
DOI: 10.1037/ort0000595
|View full text |Cite
|
Sign up to set email alerts
|

Strengths despite stress: Social-structural stressors and psychosocial buffers of depressive symptoms among U.S. Black men.

Abstract: We examined the association between social-structural stressors—racial discrimination, incarceration, and unemployment—and depressive symptoms among 578 predominantly low-income urban Black men, ages 18–45. We also examined the extent to which two protective factors—social support and problem-solving coping—moderated the relationship between social-structural stressors and depressive symptoms. Results showed that more everyday racial discrimination and incarceration, but not unemployment, significantly predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…However, a major limitation of these studies is that they are from the mother's perspective and not the sons themselves. The few studies that captured the voices of Black men regarding their wellness and development purported that the mother/son social support process is a two-way and interactive endeavor whereby sons draw heavily upon their relationship with their mothers to learn how to navigate romantic relationships (Morman & Whitely, 2012), that Black college men are not adequately prepared to address elements that impact their health and how they can improve it (Mincey et al, 2017), and that interventions to help Black men should emphasize protective factors and championed for structural interventions to reduce racial discrimination and incarceration (Del Río-González et al, 2022). One study, an examination of the help-seeking behaviors of Black men reported that 33% of their respondents used both professional services and informal support, while 14% of the men relied on professional support only, 24% of the participants used informal support only, and 29% of them did not seek help at all (Woodward et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, a major limitation of these studies is that they are from the mother's perspective and not the sons themselves. The few studies that captured the voices of Black men regarding their wellness and development purported that the mother/son social support process is a two-way and interactive endeavor whereby sons draw heavily upon their relationship with their mothers to learn how to navigate romantic relationships (Morman & Whitely, 2012), that Black college men are not adequately prepared to address elements that impact their health and how they can improve it (Mincey et al, 2017), and that interventions to help Black men should emphasize protective factors and championed for structural interventions to reduce racial discrimination and incarceration (Del Río-González et al, 2022). One study, an examination of the help-seeking behaviors of Black men reported that 33% of their respondents used both professional services and informal support, while 14% of the men relied on professional support only, 24% of the participants used informal support only, and 29% of them did not seek help at all (Woodward et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this factor must be reliably and validly measured. In Black men daily racial discrimination and incarceration are correlated with depressive symptoms; yet there is literature underscoring the strengths of Black men as a potential resource (del Río-González et al, 2022). Both the resilience (Factor 5) and cognitive–behavioral coping (Factor 2) facilitate the measurement of these assets.…”
Section: Discussionmentioning
confidence: 99%
“…If the social fabric is characterized by injustice, anomie, individualism, inequality, competition, and shaming, people can feel unworthy and isolated (Case & Deaton, 2020;O'Neil, 2022;Payne, 2017;Putnam, 2021;Sandel, 2020). In cases of discrimination against sexual minorities, for instance, we witness higher levels of psychological distress and lower levels of personal and social well-being (Del Río-González et al, 2022;Thorpe et al, 2022). The same applies in cases of discrimination against immigrants (Lincoln et al, 2021).…”
Section: Communalmentioning
confidence: 99%
“…Their very identity is denied or denigrated, and their personhood disrespected, leading to high levels of distress. Similarly, Black men who experience more everyday racial discrimination display more depressive symptoms (Del Río-González et al, 2022).…”
Section: Fairnessmentioning
confidence: 99%